Heat loss analysis of hydrodistillation of mangosteen pericarp - Tan, Evon (2014)
Mangosteen pericarp essential oil is primarily used in traditional Thai medicine and has a high commercial value due to its therapeutic properties. In this experimental work, hydrodistillation was employed as a common method of extracting essential oil. Furthermore it is economically viable and safe. Gas chromatography- flame ionization detector analysis (GC-FID) was performed for Volatile oils of mangosteen pericarp. The main constituent of the essential oil is ferulic acid. In this research, the heat loss of hydrodistillation process of mangosteen pericarp is discussed. The comparison for heat loss between different parts of Clevenger-type apparatus,such as round bottom flask (RBF) and biomass flask(BF). The heat removed by chamber (C) is 5.81 x 106 J. The heat loss in (BF) and (RBF) are 2.22x 106 J and 2.05 x 105 J respectively. The prevention of heat loss of Clevenger-type apparatus can be improved in future study by carrying out the research in large scale